2016
DOI: 10.1097/mao.0000000000000944
|View full text |Cite
|
Sign up to set email alerts
|

Is MRI Equal to CT in the Evaluation of Thin and Dehiscent Superior Semicircular Canals?

Abstract: In this series, MRI in the axial and coronal plane had a high negative predicative value for thin SSC (86%) and dehiscent SSC (97%). However, MRI cannot conclusively diagnose thin or dehiscent SSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
(9 reference statements)
2
12
0
1
Order By: Relevance
“…The positive predictive value for the use of MRI was 93.4% and the negative predictive value 83.7% in our study group. This positive predictive value was close to that found in similar studies in the literature [8,10] ; however, the negative predictive value of MRI was lower (33.3%) in a study published by Browaeys et al [10].…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…The positive predictive value for the use of MRI was 93.4% and the negative predictive value 83.7% in our study group. This positive predictive value was close to that found in similar studies in the literature [8,10] ; however, the negative predictive value of MRI was lower (33.3%) in a study published by Browaeys et al [10].…”
Section: Discussionsupporting
confidence: 49%
“…To the best of our knowledge, the first similar study on this subject was reported by Krombach et al [11] in 2004, who found that MRI had a sensitivity level of 96% and a specificity level of 98%. Subsequent studies showed similarly high sensitivity and specificity levels [8,10] .…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations